KOMPETENSI PERANGKAT DESA DAN KEPEMIMPINAN KEPALA DESA DALAM IMPLEMENTASI REFOCUSING ANGGARAN - Alimurrahman; Moh. Faisol (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
Budget refocusing is the Presidential Instruction Number 4 of 2020 concerning Refocusing Activities, Budget Reallocation, and Procurement of Goods and Services in the Context of Accelerating the Handling of Covid 19. This study aims to examine the effect of village apparatus competence and village head leadership on the implementation of budget refocusing on village governments in the Sumenep district. The object of this research is the village government in Sumenep Regency which is located in the mainland area, with a total of 106 respondents. The research data was tested using SPSS software. The results showed that the competence of village officials had an effect on the implementation of village government budget refocusing, while the leadership of the village head had no effect on the implementation of village government budget refocusing. The implication is that the competencies possessed by village officials such as education level, technical experience, and creativity become big capital in implementing a policy.